LIFE STORY OF SANTU: A NARRATIVE INQUIRY - Khatri, Man Bahadur (IJRDO-Journal of Applied Science, 2015)
Narrative is the means through which we integrate experience to explain how we have remained the sameor changed throughout our life (Trahar & Yu, 2015). It means it is used to capture the personal and humandimensions of experience over time. Human subjects have lots of incidents and experiences throughwhich they have come to the present and set their future from generation to generation. With lots of upsand downs in search of passion of life a person faces sweet and bitter experiences amid of severalfluctuations; that is the actual meaning life. This life story can be valuable and meaningful for somereaders/listeners. So, a narrative inquirer should search and explore such experiences and present in abeautiful language without killing the spirit of the narration and feeling of the informants.In search of the condition and expectation of the elderly people towards their children, I met Santu inKathmandu. While taking a phenomenological data about her life condition, expectation and desirestowards her children in her old age, she became excited to explore her life story. My meeting,communication skill and passion to listen her story encouraged her to explore more about herself.Believing Santu a representative elderly character of our society, I felt, the parts of the stories are worthyto unlock to the readers/listeners through journal article. So, I started preparing her life story throughnarrative inquiry under phenomenological approach.Santu’s life story is metaphorically compared to the mirror and mirror image; we see ourselves but whatwe see is not exactly our reality. Mirror can be cracked even with a small pushes and pulls, and so is thelife of women/girls. Mirror gets hanged wherever a man likes same is the life of women/girls. It is neverfree and independent. Moreover, their desires and willingness are never welcomed and respected inpatriarchal society. Therefore the metaphorical use of glass has covered lots of things of Santu’s life in thestory.The waves and storms of Santu’s life are explored in detail. While taking data about elderly period;expectations and desires, her childhood, youths and adulthood are also examined critically. Her love,tragedy, experience of life, children and grandchildren are also served in a fascinating way in a faithful Narrative is the means through which we integrate experience to explain how we have remained the sameor changed throughout our life (Trahar & Yu, 2015). It means it is used to capture the personal and humandimensions of experience over time. Human subjects have lots of incidents and experiences throughwhich they have come to the present and set their future from generation to generation. With lots of upsand downs in search of passion of life a person faces sweet and bitter experiences amid of severalfluctuations; that is the actual meaning life. This life story can be valuable and meaningful for somereaders/listeners. So, a narrative inquirer should search and explore such experiences and present in abeautiful language without killing the spirit of the narration and feeling of the informants.In search of the condition and expectation of the elderly people towards their children, I met Santu inKathmandu. While taking a phenomenological data about her life condition, expectation and desirestowards her children in her old age, she became excited to explore her life story. My meeting,communication skill and passion to listen her story encouraged her to explore more about herself.Believing Santu a representative elderly character of our society, I felt, the parts of the stories are worthyto unlock to the readers/listeners through journal article. So, I started preparing her life story throughnarrative inquiry under phenomenological approach.Santu’s life story is metaphorically compared to the mirror and mirror image; we see ourselves but whatwe see is not exactly our reality. Mirror can be cracked even with a small pushes and pulls, and so is thelife of women/girls. Mirror gets hanged wherever a man likes same is the life of women/girls. It is neverfree and independent. Moreover, their desires and willingness are never welcomed and respected inpatriarchal society. Therefore the metaphorical use of glass has covered lots of things of Santu’s life in thestory.The waves and storms of Santu’s life are explored in detail. While taking data about elderly period;expectations and desires, her childhood, youths and adulthood are also examined critically. Her love,tragedy, experience of life, children and grandchildren are also served in a fascinating way in a faithful Narrative is the means through which we integrate experience to explain how we have remained the sameor changed throughout our life (Trahar & Yu, 2015). It means it is used to capture the personal and humandimensions of experience over time. Human subjects have lots of incidents and experiences throughwhich they have come to the present and set their future from generation to generation. With lots of upsand downs in search of passion of life a person faces sweet and bitter experiences amid of severalfluctuations; that is the actual meaning life. This life story can be valuable and meaningful for somereaders/listeners. So, a narrative inquirer should search and explore such experiences and present in abeautiful language without killing the spirit of the narration and feeling of the informants.In search of the condition and expectation of the elderly people towards their children, I met Santu inKathmandu. While taking a phenomenological data about her life condition, expectation and desirestowards her children in her old age, she became excited to explore her life story. My meeting,communication skill and passion to listen her story encouraged her to explore more about herself.Believing Santu a representative elderly character of our society, I felt, the parts of the stories are worthyto unlock to the readers/listeners through journal article. So, I started preparing her life story throughnarrative inquiry under phenomenological approach.Santu’s life story is metaphorically compared to the mirror and mirror image; we see ourselves but whatwe see is not exactly our reality. Mirror can be cracked even with a small pushes and pulls, and so is thelife of women/girls. Mirror gets hanged wherever a man likes same is the life of women/girls. It is neverfree and independent. Moreover, their desires and willingness are never welcomed and respected inpatriarchal society. Therefore the metaphorical use of glass has covered lots of things of Santu’s life in thestory.The waves and storms of Santu’s life are explored in detail. While taking data about elderly period;expectations and desires, her childhood, youths and adulthood are also examined critically. Her love,tragedy, experience of life, children and grandchildren are also served in a fascinating way in a faithful order. Finally her experience of life as a female is presented emphatically in a poetic language in theconcluding section.